Scientific Misconduct in Breastfeeding Research at Workplace: A Narrative Review - Christopher Filbert (The Indonesian Journal of Community and Occupational Medicine, 2024)
Introduction: Breastfeeding is a crucial source of nutrition for infants, especially from 0 to 6 months. However, many working mothers struggle to provide exclusive breastfeeding due to insufficient workplace support. Although Indonesian regulations and some international policies support breastfeeding rights for working mothers, enforcement remains inconsistent, particularly in industries with high productivity demands.Method: This literature review was conducted in October 2024 using publications from 2018 to 2024. Relevant studies were identified using the Universitas Indonesia Remote Library, Google Scholar, and The Indonesian Journal of Community and Occupational Medicine (IJCOM) with the keyword “breastfeeding worker.” The review includes cases of breastfeeding rights violations by governments, companies, and the public.Results: The findings reveal significant challenges faced by working mothers in the garment industry in Cakung, North Jakarta, such as unpaid overtime and lack of adequate breastfeeding time and facilities. Similar issues were found in Ghana’s health sector, where medical workers lack support and private spaces for breastfeeding, leading to emotional stress and reduced rates of exclusive breastfeeding.Conclusion: There are still numerous workplaces that fail to comply with breastfeeding policies, despite existing regulations supporting workers’ rights. Collaboration between governments and workplace management is essential to ensure the availability of breastfeeding facilities that support the well-being of mothers and infants without compromising productivity.